Academic Senate Minutes 2001-08-30 - Academic Senate:::::::::
Agenda and Minutes Approved. Report from the Chair. New members introduced. Resolution for Phil McGough approved. Faculty Emeritus Policy approved. Senate End of Year Report noted. Catherine Nelson and Tim Wandling elected to serve on Executive Committee. Amendments to ByLaws first reading. Compensation for Lecturers referred to FSAC. Report from Lou Levy, Senior Director of Enrollment Services, Report from Saeid Rahimi, Dean of Natural Sciences on the Masters Program in Engineering and Computer Science. List of faculty eligible for Emeritus status approved. Reports from Provost, Chair- Elect, Statewide Senator, President of AS, APC, FSAC, and SAC.